2022
DOI: 10.1039/d2ra06053a
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of metal loading on the performance of Co catalysts supported on mixed MgO–La2O3 oxides for ammonia synthesis

Abstract: Co supported on mixed MgO–La2O3 oxides as efficient and stable catalysts for ammonia synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…For the DP catalyst, no change in the SSAred value was observed. Further overheating under these conditions for 20 and 30 h did not cause any further changes in the specific surface area of The superior performance of the CoCeBa catalysts for ammonia synthesis was revealed by comparison to the literature results with similar reaction conditions (Table S2) [34][35][36][37][38][39][40]. In particular, the ammonia formation rate over CoCeBa catalysts reached 3.17-3.35 g NH3 g cat −1 h −1 , which was almost three times that of commercial iron catalyst (ZA-5).…”
Section: Evaluation Of Catalyst Properties During Stability Studiesmentioning
confidence: 78%
“…For the DP catalyst, no change in the SSAred value was observed. Further overheating under these conditions for 20 and 30 h did not cause any further changes in the specific surface area of The superior performance of the CoCeBa catalysts for ammonia synthesis was revealed by comparison to the literature results with similar reaction conditions (Table S2) [34][35][36][37][38][39][40]. In particular, the ammonia formation rate over CoCeBa catalysts reached 3.17-3.35 g NH3 g cat −1 h −1 , which was almost three times that of commercial iron catalyst (ZA-5).…”
Section: Evaluation Of Catalyst Properties During Stability Studiesmentioning
confidence: 78%
“…It is also worth noting that in light of the present research, the activity of these catalysts is driven by two main factors: the basicity of the lanthanide support, as it determines the TOF of the active phase, and the active phase content, which determines the number of active sites as well as the cobalt particle size. In the study [140], concerning Co/MgO-La 2 O 3 systems differing in cobalt loading, it was presented that regardless of the cobalt content, the TOF values for all systems were very similar (0.025 s −1 at 6.3 MPa and 400 • C), which was achieved at an average cobalt particle size of ca. 20 nm.…”
Section: Cobalt-based Catalystsmentioning
confidence: 95%
“…Broad research on cobalt catalysts deposited on mixed magnesium-lanthanide oxides was conducted by Ronduda et al [136][137][138][139][140][141][142][143][144]. They demonstrated that using mixed supports results in very active catalysts, similar to ruthenium-based systems [96][97][98][99].…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
“…A 40 wt% Co loading was chosen based on our previous work. 50 Typically, a suitable amount of Co(NO 3 ) 2 ·6H 2 O (Acros Organics, 98+%) was dissolved in distilled water under stirring. Then, the oxide support was added to the above precursor solution.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we present the continuation of our comprehensive studies concerning cobalt catalysts supported on mixed MgO-La 2 O 3 oxides. [45][46][47][48][49][50] This study addresses the effect of Ca and Ba addition on the physicochemical properties and catalytic performance of the Co ammonia synthesis catalysts. This work aims to determine the location, state, and effect of dopants on the catalytic property of the Co/MgO-La 2 O 3 systems.…”
Section: Introductionmentioning
confidence: 99%